Assessing the attitudes of Greek nurses toward computerized dementia screening - Zygouris, Stelios; Gkioka, Mara; Moraitou, Despina; Teichmann, Birgit; Tsiatsos, Thrasyvoulos; Papagiannopoulos, Sotirios; Tsolaki, Magda (Journal of Alzheimer's disease, 2020)
Background: Despite the abundance of research on computerized dementia screening tests, the attitudes of hospital personnel toward this screening method have not been investigated. Objective: 1) To conduct a confirmatory factor analysis of the first
Gesehen am 13.01.2021